1970
DOI: 10.1021/ja00707a013
|View full text |Cite
|
Sign up to set email alerts
|

Ligand substitution catalysis via hard acid-hard base interaction

Abstract: The catalytic decomposition of hydrogen peroxide by Cu-histidine complexes has been investigated in the pH range 6-8 in phosphate buffer (0.013 M) by a differential manometric technique. The kinetic data on the initial rates of 02 evolution are explained by a second-order rate equation, first order with respect to the 1:1 Cuhistidine chelate, and first order with respect to the " anion. Chemical and spectrophotometric studies indicated that the reaction mechanism involves a cupric-cuprous couple.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…[Cu(CIoHsN2)(PF202)2] These crystals did not form from analogous solutions in which the solvent had been rigorously dried. The formation of PF20~-from hydrolysis of PF6 in the presence of transition metal complexes has been reported previously (White, Thompson & Maitlis, 1977;Bruce, Cifuentes, Grundy, Liddell, Snow & Tiekink, 1988;Clark & Jones, 1970, 1971. X-ray analysis of these colorless crystals shows them to be (bpy)Cu(PF202)2.…”
Section: Introductionsupporting
confidence: 72%
“…[Cu(CIoHsN2)(PF202)2] These crystals did not form from analogous solutions in which the solvent had been rigorously dried. The formation of PF20~-from hydrolysis of PF6 in the presence of transition metal complexes has been reported previously (White, Thompson & Maitlis, 1977;Bruce, Cifuentes, Grundy, Liddell, Snow & Tiekink, 1988;Clark & Jones, 1970, 1971. X-ray analysis of these colorless crystals shows them to be (bpy)Cu(PF202)2.…”
Section: Introductionsupporting
confidence: 72%
“…It is known that the hydrolysis of other complexes of fluoro acids also involves H + ions, as well as the other polarizing cations [26][27][28][29][30][31]. In the recent works of Ponikvar et al [30,31], it was shown that hydrolysis of bonds to fluorine is often assisted by acids.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, very few reports concerning the transformations of the catalyst are available, and discussions on the interaction between catalyst and IL are speculative so far. Here, we suppose that the preferential combination of the Sb of the catalyst and the F of the PF 6 − decreased the catalyst activity 34…”
Section: Resultsmentioning
confidence: 99%